Effect of some plant growth regulators and different explants types on callus induction in saffron - Khadijeh Bagheri; Pejman Azadi; Mitra Gholami; Massoud Mir Masoumi (Zirā̒at va Fanāvarī-i Za̒farān, 2017)
Saffron (Crocus sativus L.) is the world's most expensive spice. Moreover, it is important since it contains various drug metabolites. Saffron is a triploid (2n=3X=24) and sterile plant and it does not have any viable seeds. Because of the sterility, classical breeding of this plant is limited. Developing an efficient callus induction protocol is studied for two reasons, i.e. molecular breeding and the production of secondary metabolites. In order to provide a suitable callus induction protocol, establishment of corms was considered. Five different treatments were applied to sterilization of corms. Thin cell layer explants with approximately 1 mm thickness and typical explants with approximately 1 cm thickness were prepared from sterilized corms. For callus induction, different explants were planted in MS medium containing different concentration of 2, 4-D, BAP and NAA. Then, they were incubated in dark conditions at 20 ±20C for 3 months. The results showed that the use of Benomyl fungicide, followed by surface sterilization using sodium hypochlorite (2.5 %) was the best sterilization treatment. The highest survival rates of explants (90%) were observed in this treatment and all explants were free of contamination. The highest amount of callus induction (75%) was obtained in MS medium supplemented with 2mg/l NAA and 0/5 mg/l BAP from thin cell layer of basal corm. The same result was observed with 1mg/l 2, 4-D from typical explants of basal corm. The results obtained from this study show that the thin cell layer explants are suitable explants because of the high amount of callus formation and the advantages for gene transfer studies. The results showed that the use of Benomyl fungicide, followed by surface sterilization using sodium hypochlorite (2.5 %) was the best sterilization treatment. The highest survival rates of explants (90%) was observed in this treatment and all explants were free of contamination. The highest amount of callus induction (75%) was obtained in MS medium supplemented with 2mg/l NAA and 0/5 mg/l BAP from thin cell layer of basal corm. The same result was observed with 1mg/l 2,4-D from typical explants of basal corm. Our results showed that the thin cell layer explants are suitable explant because of high amount of callus formation and advantages for gene transfer studies.